PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, LINGKUNGAN KERJA DAN FASILITAS KERJA TERHADAP KINERJA KARYAWAN HOTEL IBIS PADANG - Dewi, Aminar Sutra; Yoliandra, Yoliandra (JURNAL PUNDI, 2024)
This study aims to analyze the influence of leadership style, organizational culture, work environment, and work facilities on the performance of employees at Hotel Ibis Padang. This research uses a quantitative method. The population in this study consists of all employees of Hotel Ibis Padang. The number of sample members was determined using the total sampling formula, resulting in 74 respondents. The data collection method used a questionnaire distributed to the employees of Hotel Ibis Padang. The data used in this research is primary data. The hypothesis in this study was tested using multiple regression analysis. The research results show that leadership style has a positive and significant impact on employee performance, organizational culture has a positive and significant impact on employee performance, work environment has a positive and significant impact on employee performance, and work facilities have a positive and significant impact on employee performance. Keywords: Leadership Style, Organizational Culture, Work Environment, Work Facilities, Employee Performance